Classification and Treatment Strategies of Concomitant Fibular Column Injuries in Tibial Plateau Fractures. (7th September 2021) - Yao, Xiang; Lv, Bin; Hu, MinJie; Yuan, Jishan; Fan, Xiaochen; Zhou, Kaihua; Tang, JiLei; Wang, Lei
Abstract : Background . About 1/3 of tibial plateau fractures are associated with proximal fibula fractures, but most proximal fibula fractures are often ignored. The aim of this study was to precisely explain the classification and treatment strategies of six injury types of the fibular column associated with tibial plateau fractures. Methods . Patients with ipsilateral proximal fibula and tibial plateau fractures treated in our hospital were retrospectively reviewed from Aug 2007 to Mar 2020. Two experienced surgeons and two radiologists divided fibular column injury into 6 injury types according to the AO classification and four-column nine-segment classification. The treatment scheme (surgically treated or conservatively treated) was also recorded. Results . In total, 355 proximal fibula fractures were included. Type 2 fibular head fracture was the most common type of injury in 122, and the segregate of superior tibiofibular syndesmosis was the rarest type in 3. In avulsion injury proximal of fibular pattern, the proportion of patients who need surgical intervention is the highest. Conclusions . Six injury types in the four-column nine-segment classification covered all types of bony and soft tissue injuries of the fibular column and concisely explained the injury mechanism. The classification is helpful for the precise judgement and decision-making of the concomitant fibular column injuries in tibial plateau fractures.